Measuring crowding-related comfort in public transport - Çelebi, Dilay; İmre, Şükrü (Informa UK Limited, 2020)
In this paper we focus on the estimation of crowding in public transport – specifically urban rail systems – and its effect on perceived comfort. It is different from similar studies in the method ...
Keywords: public transport; discomfort; mode - subway/metro; operations - crowding; urban rail; crowd density function; Istanbul metro; place - urban; Crowding; mode - rail; place - asia; ridership - perceptions